THE INVISIBILITY OF INDIGENOUS PEOPLES - de Goveia, Andre Ribeiro; Rech, Nair Gonçalves; Marques, Matheus Sousa da Silva; dos Santos, Osiana Lustosa; da Silva, Bruno Batista; Trindade, Genivaldo Rodrigues; Gouveia, Joselma dos Reis; de Amorim, Orcimar Sousa Gomes; Menezes, Patricia Oliveira; Souza, Luciano Paulo de Almeida; Borges, Samuel Marques; Meneses, Karinne Oliveira; et al. (Seven Editora, 2025)
This study analyzes the historical and contemporary processes of invisibility of indigenous peoples in Brazil, focusing on the construction of brown identity as a reflection of miscegenation and its relationship with the denial of indigenous roots. Adopting a qualitative and bibliographical approach, it investigates how colonial and post-colonial practices shaped racial and cultural categories in the country, promoting the erasure of ethnic specificities. The work also discusses the current challenges for the appreciation and recognition of indigenous identities, highlighting the limitations of public policies, educational representations and the fight for territorial and cultural rights. It is concluded that, despite the obstacles, indigenous populations have shown themselves to be resilient and active in asserting their identities, contributing indispensably to the construction of a more plural and inclusive society. The research reaffirms the urgency of actions that deconstruct historical prejudices and promote effective reparation, ensuring the preservation of indigenous cultures and knowledge.DOI: https://doi.org/10.56238/sevened2025.026-011